Daya Saing Udang Indonesia di Pasar Internasional: Sebuah Analisis dengan Pendekatan Pangsa Pasar Menggunakan Model Ekonometrika - Tajerin Tajerin; Mohammad Noor (Economic Journal of Emerging Markets, 2004)
Until the early 1997’s, the competition of shrimp in international markets has been dominated by Indonesian shrimp. It is believed that Indonesian shrimp is less competitive that of Thailand and ROW (rest of the world) shrimp the markets. The objectives of the present study are to analyze the competitiveness of Indonesian shrimp in the international markets and to formulate strategic for market development. A Market-share approach is used to estimate the competitiveness of shrimp from Indonesia, Thailand and the rest of the world in Japanese and the United States markets. The results show that Indonesian shrimp is relatively competitive in comparison development for Indonesian shrimp necessary. The Indonesian schrimp has been dominant in Japanese and United Nation markets. In the United Nation, Indonesian Schrimp was significants competitive with Thailand Scrimp that it potential to develompment, while in Japanese market, ROW schrimp to be potential competitive for Indonesian. In European Union market (France, Spanyol and Italian), Indonesian schrimp has potential posses to moved ROW schrimp. Keywords: Competitive Advantages, Shrimp, International Market, Export.